2015
DOI: 10.1128/iai.02848-14
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Hemolysin and Cytotoxic Necrotizing Factor Type 1 (CNF1) Reduce Bladder Inflammation in a Mouse Model of Urinary Tract Infection with Toxigenic Uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC) is the leading cause of cystitis. Cytotoxic necrotizing factor 1 (CNF1) and hemolysin (Hly) are toxins made by approximately 50% of UPEC isolates. CNF1 and Hly contribute to the robust inflammatory response in the bladders of mice challenged with UPEC strain CP9. We hypothesized that antibodies against CNF1 and/or Hly would reduce cystitis caused by CP9. To test this theory, we immunized female C3H/HeOuJ mice subcutaneously with a genetically derived Hly toxoid or genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…A super-saturating transposon library generated to assess genes of importance in UPEC bacterial fitness, inoculated intravenously, did not recover transposon mutants of HlyA (100) . Although the authors do not specifically report each (1,101,102) . Characterization of the mechanism of HlyA pore formation or identification of a receptor for the toxin could not only lead to the development of therapeutic treatments for severe UPEC infections, but would benefit a much larger field, as members of the RTX toxin family span a variety of human pathogens, including those that infect the urinary tract, blood stream, intestinal tract and respiratory tract.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…A super-saturating transposon library generated to assess genes of importance in UPEC bacterial fitness, inoculated intravenously, did not recover transposon mutants of HlyA (100) . Although the authors do not specifically report each (1,101,102) . Characterization of the mechanism of HlyA pore formation or identification of a receptor for the toxin could not only lead to the development of therapeutic treatments for severe UPEC infections, but would benefit a much larger field, as members of the RTX toxin family span a variety of human pathogens, including those that infect the urinary tract, blood stream, intestinal tract and respiratory tract.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In recent years, pioneering studies have provided evidence that CNF1 has the capacity to promote inflammation, stimulate host immunity and function as a potent immunoadjuvant [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Nevertheless, the immunostimulatory properties of the toxin are not fully understood and little is known about its direct effects on different immune cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Infection studies have further reported that CNF1 has the capacity to promote inflammation in vivo, indicating that the toxin also possesses immunostimulatory properties [ 10 , 11 , 12 , 13 ]. In line with this conclusion, CNF1 has been shown to be a potent immunoadjuvant that can augment antigen-specific adaptive immune responses and host protection [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct contact between S. marcescens Db11 and infected C. elegans was required for killing effect, indicating that the function of hemolysins synergized other components in S. marcescens Db11 for pathogenicity (Kurz and Ewbank, 2000 ; Kurz et al, 2003 ). Moreover, hemolysins attacked various immune cells as an immune evasion strategy (Smith et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%